Characterization of the dCaMKII-GAL4 driver line whose expression is controlled by the Drosophila Ca(2+)/calmodulin-dependent protein kinase II promoter. - Takamatsu, Y.; Nakagoshi, H.; Rachidi, M.; Lopes, C.; Nishida, Y.; Ohsako, S. (Cell and Tissue Research, 2002)
Transgenic flies that can drive GAL4 expression under the control of the 7 kb 5'-region of the Drosophila Ca(2+)/calmodulin-dependent protein kinase II (dCaMKII) gene (dCaMKII-GAL4) were established. Characteristic features of this dCaMKII-GAL4 driven reporter expression were compatible with the endogenous dCaMKII expression pattern: The dCaMKII-GAL4 driven reporter gene was expressed preferentially in the central nervous system of the embryo and larvae. Reporter expression was also observed in the brain, thoracic ganglion, and gut of the adult. The whole-brain distribution and projections of dCaMKII-GAL4-expressing cells in the adults were visualized three-dimensionally by using UAS-linked reporter genes. Prominent signals of nuclear-localized beta-Gal reporter gene expression were found in extensive brain regions, especially in the Kenyon cells of the mushroom body (MB), cells in the pars intercerebralis, and subesophageal ganglion (SOG). tau reporter gene expression highlighting neurite projections was detected in the MB lobes, median bundle, antennal lobe glomeruli, and fibers of clusters in the SOG, ventrolateral protocerebrum and superior lateral protocerebrum. These observations agree with those of a previous study mapping the dCaMKII-dependent memory circuits in courtship conditioning. Interestingly, green fluorescent protein reporter gene expression in adult MB lobes was predominantly observed in the alpha and beta lobes with a core-deficient pattern, but not in the alpha' and beta' lobes, similar to Fasciclin II immunoreactivity.